2002
DOI: 10.1128/jvi.76.15.7705-7712.2002
|View full text |Cite
|
Sign up to set email alerts
|

Daxx-Mediated Accumulation of Human Cytomegalovirus Tegument Protein pp71 at ND10 Facilitates Initiation of Viral Infection at These Nuclear Domains

Abstract: in normal cells. This result strongly suggests that pp71 and Daxx are essential for HCMV transcription at ND10. Lack of Daxx had the effect of reducing the infection rate. We conclude that the tegument transactivator pp71 facilitates viral genome deposition and transcription at ND10, possibly priming HCMV for more efficient productive infection.Nuclear domains 10 (ND10), also called PML nuclear bodies or PML oncogenic domains (PODs), represent intranuclear accumulations of several proteins, including the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
126
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(138 citation statements)
references
References 33 publications
9
126
2
1
Order By: Relevance
“…7 and 8), but a role for ND10 in their transcription has not been fully established. For example, although parental human cytomegalovirus and simian virus 40 genomes are found in association with ND10 (35)(36)(37), the levels of viral RNA were unaltered in cells lacking PML and ND10 (37,38), in contrast to our findings for PV.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…7 and 8), but a role for ND10 in their transcription has not been fully established. For example, although parental human cytomegalovirus and simian virus 40 genomes are found in association with ND10 (35)(36)(37), the levels of viral RNA were unaltered in cells lacking PML and ND10 (37,38), in contrast to our findings for PV.…”
Section: Discussioncontrasting
confidence: 56%
“…Capsid proteins have not previously been implicated in the deposition of a viral genome at ND10. The example of the human cytomegalovirus (HCMV) tegument protein, pp71, which functions to activate viral immediate early transcription (43) and has been shown to be necessary for genome localization and transcription at ND10 (35), may have some similarities, but, as previously mentioned, the absence of ND10 does not affect the level of HCMV transcripts (38). L2 is not known to possess any transcriptional activity, which suggests that its main function in this process is to localize the DNA to a site that favors transcription.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by the alterations in PML bodies described during DNA and RNA virus infections (reviewed in Doucas and Evans, 1996). In cells infected with Hepatitis delta virus , herpes simplex virus-1, human cytomegalovirus (Ishov et al, 2002), or human papilloma virus (Becker et al, 2004), the virus localizes to enlarged PMLs, and in some cases subsequently disrupts PML bodies (Everett and Maul, 1994). It should be stressed that viruses are highly ordered protein aggregates.…”
Section: Relationship Between Nuclear Aggregates and Pml Bodiesmentioning
confidence: 93%
“…Our data further demonstrate that the nuclear release of DAXX increases its association with FADD, which may serve as an explanation for the proapoptotic effects of SENP1. The question of whether this is the only mechanism by which DAXX exerts its effects in RA SFs, however, remains to be answered, because it has been shown that DAXX may also function as an adaptor molecule that recruits other proteins to PML NBs (24) and more recent data have demonstrated a role for DAXX as a transcriptional repressor of key transcriptional factors. In this context, the observation that DAXX interacts with Smad4 and represses its transcriptional activity (25) as well as data showing that the interaction of SUMO-1-modified CREB-binding protein (CBP) with DAXX mediates SUMO-dependent transcriptional regulation of CBP (26) are certainly of importance.…”
Section: A Upper and B Upper)mentioning
confidence: 99%